Bordering Through Biosecurity: Wild Boars and Veterinary Fences in the German-Polish Borderlands - Fleischmann, Larissa (DIE ERDE – Journal of the Geographical Society of Berlin, 2025)
This article analyzes how the “risky” mobilities of animals and viruses provoke government reactions that result in bordering processes: From 2020 onwards, German authorities erected hundreds of kilometers of fence along the Eastern border with Poland in response to the spreading of African swine fever (ASF), a highly contagious viral disease that affects both wild boars and domesticated pigs. The government’s main intention behind fencing was to secure the German borderline against the unwanted border crossings of potentially infected wild boars from Poland. At this point in time, the animals were framed as a disease reservoir, while their wayward spatial movements were depicted as a biosecurity threat to the export-dependent German pig sector. Drawing on qualitative fieldwork in the state of Saxony, the article illustrates how government actors employed three techniques seeking to depoliticize the erection of veterinary fences, presenting them as an apolitical matter of concern, while withdrawing them from public scrutiny and contestation: first, re-scaling authority to the sub-national level; second, securitization; and third, disinformation. Yet, adopting a more-than-human approach to the study of borders, the article also points out how a number of human and nonhuman entities forged wayward relations that worked towards a repoliticization of the fences, while counteracting government intentions in the management and control of disease.